THE BASIS OF MASS MEDIA - Abdurahmonova, S. (Main Issues Of Pedagogy And Psychology, 2013)
The problem of raising the professional level of journalists are represented in the article. The need for analytical programs in the media are mainly stressed by the author. The specific areas of the media in the modern world are identified in the article.